SELF-HELP GROUPS ON STRESS LEVEL OF INMATES IN CORRECTIONAL INSTITUTIONS - akbar amin abdullah (STIKES DUTAGAMA KLATEN, 2020)
While locked in correctional institutions, inmates' space is limited and isolated from the community. This situation can be a stressor that causes stress on inmates. The stress felt by the individuals can cause an effort to react to the stress experienced. This reaction is an activity to make adjustments to certain stimulatory situations, which if not done properly will cause physical and psychological disorders. The purpose of this study was to analyze the effect of self-help groups on the level of depression in inmates of correctional institutions. The design of research used quasi experiment with one group pretest - posttest. 20 respondents were divided into 4 self help groups that were held with frequency of 6 times in 3 weeks to solve issues. Data was analyzed using Wilcoxon test. The results showed that there was an effect of self-help groups on the stress level of inmates in correctional institutions marked by a p-value of 0.002 p <0.05. Experience and information obtained during self-help groups can be used as a source of coping for inmates so that adaptive coping can be achieved and stress problems can be overcome.